The hunt for the hippocampus - Blanco, Marivi S.; San Diego, Ramus (Manila : Tahanan Books for Young Readers, 1996)
Join junior Filipino detectives Jenny and her brother Jay, as they encounter the ghost of a woman accused of witchcraft over three hundred years ago. The witch summons a sea monster known as the Hippocampus to exact her deadly revenge and Jenny and Jay face a terror-drenched climax at sea!
Primary
Keywords: Mystery and detective stories; Fantasy; Ghosts -- Juvenile fiction; Witches -- Juvenile fiction; Witches -- Juvenile fiction